Anthropomorphic Figuration of the Virus and the HIV/AIDS Disease: A View from the Scientific Humanities - Arriaga Ornelas, José Luis (2024)
The hypothesis that viruses are not devoid of humanity is reviewed. This is done within the framework of what Latour defines as “scientific humanities”, which call into question the idea of autonomy of sciences and techniques The procedure followed consists of the analysis of documents produced to refer to the Human Immunodeficiency Virus (HIV) and the disease it causes, AIDS, paying special attention to how these discursive constructions fill it with humanity until it gives it an anthropomorphic figuration. The objective is to show that today living human life can no longer do without thinking and acting in relation to viruses, because they have entered the “surrounding world” of human beings, which has relevant political and social repercussions and that has been recently discussed from various disciplines. It would not be a solely medical relationship, restricted to laboratories, hospitals and treatments. Among the findings offered are, on the one hand, the evidence that viruses are not only scientific objects, but bearers of significance; and, on the other, the exhibition of how human beings trigger their symbolic-significant metamorphosis turning them into characters capable of modifying the social body, the imaginary, symbols, relationships between people, institutions, and even public policies.